Ablation or Resection for Colorectal Liver Metastases? A Systematic Review of the Literature - Kron, Philipp; Linecker, Michael; Jones, Robert P.; Toogood, Giles J.; Clavien, Pierre-Alain; Lodge, J. P. A. (Frontiers in Oncology, 2019)
Abstract Background Successful use of ablation for small hepatocellular carcinomas (HCC) has led to interest in the role of ablation for colorectal liver metastases (CRLM). However, there remains a lack of clarity about the use of ablation for colorectal liver metastases (CRLM), specifically its efficacy compared with hepatic resection. Methods A systematic review of the literature on ablation or resection of colorectal liver metastases was performed using MEDLINE, Cochrane Library, and Embase until December 2018. The aim of this study was to summarize the evidence for ablation vs. resection in the treatment of CRLM. Results This review identified 1773 studies of which 18 were eligible for inclusion. In the majority of the studies, overall survival (OS) and disease-free survival (DFS) were significantly higher and local recurrence (LR) rates were significantly lower in the resection groups. On subgroup analysis of solitary CRLM, resection was associated with improved OS, DFS and reduced LR. Three series assessed the outcome of resection vs. ablation for technically resectable CRLM, and showed improved outcome in the resection group. In fact, there were no studies showing a survival advantage of ablation compared to resection in the treatment of CRLM. Conclusions Resection remains the “gold standard” in the treatment of CRLM and should not be replaced by ablation at present. This review supports the use of ablation only as an adjunct to resection and as a single treatment option when resection is not safely possible.